ASSOCIATING LAND WITH PEOPLE: LAND AND COLLECTIVE IDENTITY AMONG THE SUKU ASLI OF SUMATRA - Takamasa Osawa (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2017)
This paper explores some of the ways in which the connection between people and space has changed among the Suku Asli (‘Indigenous People’) living in Sumatra. The eastern coasts of Sumatra, Indonesia, are low and marshy lands, which are divided by numerous brackish rivers, and covered by vast mangrove forests. This region was a largely unpopulated area where some orang asli (‘indigenous’) groups and a few Malay people lived before the colonial era. ‘Suku Asli’ are one of the orang asli groups who were known as ‘Orang Hutan’ (Forest People) in the past - they lived along the banks as well as estuaries of rivers. Although their space was always somewhat of a ‘niche’ and did not exhibit any clear boundaries in terms of individual or collective ownership, the Suku Asli were confronted with the necessity to establish the boundaries after the state independence. However, their way of ensuring their land was not a simple one to claim their antecedent right of the land. At first in the 1960s, they joined the government deforestation programmes of hinterland ‘for giving lands to our children and grandchildren’. More recently, through the involvements with the ‘indigenous movement’ and environmentalism, they have tried to claim the rights of economically-worthless coastal marshy lands as their ‘ancestral lands’. In this paper, I try to describe the historical changes in the relation between the Suku Asli and the space surrounding them by focusing on the cultural 'logic' that is used to explain and support their connection to it - a 'logic' that enables the Suku Asli to conceptualize their relationship to land as both an embodiment and a manifestation of their collective identity.